Preparation method and application of lignin deep eutectic gel
By combining deep eutectic solvent with lignin, anhydrous lignin deep eutectic gel is formed, which solves the performance problems of lignin-based hydrogels at high and low temperatures, and achieves high mechanical strength, excellent adhesion performance and Wide temperature strain sensing performance, suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411324832.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-10
AI Technical Summary
The existing lignin-based hydrogels have deteriorated performance due to moisture evaporation at high temperatures, and their structures are damaged by ice crystal formation at low temperatures, making them difficult to use for a long time, and their structure is complex and their water solubility is poor, so they have failed to fully utilize their potential.
Deep eutectic solvent is used to combine with lignin, and the mixture of hydrogen bond acceptor and hydrogen bond donor is mixed and heated, and crosslinking agent and initiator are added to form anhydrous lignin deep eutectic gel to enhance its mechanical strength and Adhesion properties and improve anti-freeze and UV resistance through catechol groups and aromatic compounds of lignin.
The prepared lignin deep eutectic gel has high conductivity, excellent adhesion properties and wide temperature strain sensing properties. It can maintain stable performance in the temperature range of -20-80℃, and is suitable for wearable devices and biological Electrode patches and other fields.
Smart Images

Figure CN119285873A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogels, and specifically relates to a method for preparing a lignin deep eutectic gel with high adhesion and wide temperature strain sensing, and also relates to the application of the lignin deep eutectic gel with high adhesion and wide temperature strain sensing as a conductor in sensors and bioelectrode patches. Background Art
[0002] Lignin is a natural high molecular polymer rich in active functional groups such as alcoholic hydroxyl, phenolic hydroxyl and methoxyl groups. It can generate stable dynamic free radicals and provide a large number of hydrogen bonds, which help promote the transfer of conductive ions in the matrix, thereby improving the conductive stability of the sensor. Therefore, lignin-based hydrogel sensors show high practical value in applications such as smart electronic devices.
[0003] Hydrogel is a polymer material with a three-dimensional network structure that has good flexibility, stretchability and biocompatibility. It has attracted much attention in many fields such as energy and chemical industry, biomedicine and artificial intelligence. Adding lignin to hydrogel can be used as a structural filling material to enhance the mechanical strength of the hydrogel. In addition, it can also enhance the adhesion and UV resistance of the hydrogel. Yang et al. used lignin, zinc chloride and acrylic acid to prepare a lignin-based hydrogel with high tensile stress, high conductivity and UV resistance, which can be used in flexible wearable devices; Xiu et al. used silver nanoparticles, lignin, sodium alginate and polyacrylamide to prepare a high-strain and ultra-sensitive hydrogel sensor, which has great application potential in sensing devices. However, due to the complex structure and poor water solubility of lignin, it is difficult to be fully utilized. In addition, the use of lignin-based hydrogels in high temperatures will cause the loss of performance due to the evaporation of some water, and the use in low-temperature environments will destroy the hydrogel structure due to the formation of ice crystals. Therefore, in order to enable the long-term use of sensing devices, it is necessary to develop a hydrogel that has high mechanical properties, adhesion properties, high temperature resistance and anti-freezing.
[0004] At present, deep eutectic solvents have become an ideal substitute for other organic solvents and ionic liquids due to their simple synthesis process, strong thermal stability and low toxicity. In addition, deep eutectic solvents can dissolve lignin in large quantities and are widely used in lignin extraction and classification. In this study, lignin was used as a functional additive and the multiple advantages of deep eutectic solvents were utilized to develop a high-adhesion, wide-temperature strain-sensing lignin deep eutectic gel. This gel has high mechanical strength, excellent adhesion, stable and obvious sensing signals and a wide temperature range, and has broad development potential in many fields such as wearable electronic devices, bioelectrode patches and human-computer interaction. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the hydrogel in the prior art, thereby providing a lignin deep eutectic gel, which does not contain water and is therefore not affected by water evaporation and has higher stability; at the same time, it has excellent electrical conductivity and adhesion properties, and has wide temperature strain sensing performance, and has great potential in the fields of human health monitoring, motion monitoring, and high and low temperature harsh environment monitoring.
[0006] In order to solve the above technical problems, the present invention is implemented through the following technical solutions.
[0007] The first aspect of the present invention provides a method for preparing a lignin deep eutectic gel, comprising the following steps:
[0008] (1) mixing a hydrogen bond acceptor and a hydrogen bond donor, and heating the mixture to obtain a solution A;
[0009] (2) placing lignin and a gel precursor in solution A and stirring and mixing them uniformly to obtain solution B;
[0010] (3) Add the crosslinking agent and initiator to solution B, stir vigorously to make it uniform, and then heat to polymerize.
[0011] Preferably, the hydrogen bond acceptor in step (1) is selected from one or more of lithium chloride, zinc chloride, magnesium chloride, ferric chloride and aluminum chloride.
[0012] Preferably, the hydrogen bond donor in step (1) is selected from one or more of ethylene glycol and glycerol.
[0013] Preferably, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor in step (1) is 1:3-20; more preferably, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:6-18; most preferably, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:14.
[0014] Preferably, the heating reaction in step (1) is carried out at a temperature of 60-80°C and for a time of 2-4 hours.
[0015] Preferably, the lignin in step (2) is selected from sodium lignin sulfonate. Sodium lignin sulfonate is soluble in many solvents and can ionize sodium ions to provide conductivity.
[0016] Preferably, the gel precursor in step (2) is selected from one or more of acrylamide, acrylic acid, and N-isopropylacrylamide.
[0017] Preferably, in step (2), the mass volume ratio of lignin to solution A is 0-0.2:1; more preferably, the mass volume ratio of lignin to solution A is 0.04-0.16:1; most preferably, the mass volume ratio of lignin to solution A is 0.12:1.
[0018] It should be understood that, unless otherwise specified, the "mass-to-volume ratio" in the context of the present invention should be understood in a conventional manner in the art, that is, the ratio of the mass of the solid substance (in g) to the liquid volume (in mL). For example, when the "mass-to-volume ratio of lignin to solution A is 0.1:1", if the amount of lignin added is 0.1 g, the amount of solution A added is 1 mg.
[0019] Preferably, in step (2), the mass volume ratio of the gel precursor to solution A is 0.5-1:1; more preferably, the mass volume ratio of the gel precursor to solution A is 0.9:1.
[0020] Preferably, the initiator in step (3) is selected from ammonium persulfate. Ammonium persulfate can be dissolved relatively quickly in a deep eutectic solvent.
[0021] Preferably, the cross-linking agent in step (3) is selected from N,N-methylenebisacrylamide.
[0022] Preferably, in step (3), the amount of the initiator is 0.1-1 wt% of the gel precursor; the amount of the cross-linking agent is 0.01-0.4 wt% of the gel precursor.
[0023] Preferably, the temperature of the heating polymerization in step (3) is 60-80°C and the time is 2-4 hours. At this temperature and time, the gel is formed ideally, has no pores, and has a smooth surface.
[0024] Preferably, the heating polymerization in step (3) is carried out in a vacuum drying oven.
[0025] The second aspect of the present invention provides a lignin deep eutectic gel prepared according to the above preparation method.
[0026] The third aspect of the present invention provides the use of the lignin deep eutectic gel prepared according to the above preparation method in the preparation of electronic components.
[0027] Preferably, the electronic components include but are not limited to one or more of sensors and bio-electrode patches.
[0028] The overall idea of the present invention is as follows: deep eutectic solvent has a strong solvent capacity for each gel precursor and lignin, and deep eutectic solvent has the advantages of being non-toxic, tasteless, easy to prepare, easy to recycle, stable in nature, and not easy to volatilize. There is no need to worry about water loss due to long-term exposure to the air, and the service life of the gel can be extended. Deep eutectic solvent also has antifreeze ability, and can still ensure the normal use of the gel in an ultra-low temperature environment. Lignin has a large number of catechol groups that can enhance the adhesion of the gel. In addition, lignin also has the function of supporting the gel carrier to improve the mechanical properties of the gel. The addition of lignin also enables the gel to obtain UV resistance, antibacterial properties and photothermal conversion capabilities.
[0029] In the lignin deep eutectic gel system obtained by the present invention, the deep eutectic solvent contains a large number of hydrogen bonds, which can dissolve a large number of polar substances rich in hydrogen bonds, and the deep eutectic solvent has the effect of hindering the formation of ice crystals, providing the gel with antifreeze properties. The lignin deep eutectic gel system of the present invention has a large number of polydopamine containing catechol groups, which can provide a viscous component. The catechol / quinone groups in the lignin can be converted by oxidation-reduction, which can provide the gel with durable and repeatable adhesion. Lignin contains a large number of hydroxyl functional groups, which can form a large number of dynamic hydrogen bonds between each gel precursor and the deep eutectic solvent, thereby improving the mechanical properties of the gel and giving it a stronger self-healing ability. The cyclic conjugated double bond structure characteristics can absorb ultraviolet rays and convert them into heat energy for release. Lignin contains a large number of aromatic compounds, so it has a strong ultraviolet absorption ability and the ability to convert light energy into heat energy. Adding lignin into the gel can give the gel the same properties. Since lignin is stable and difficult to decompose, it also has certain antibacterial ability. The present invention uses various gel precursors as gel carriers, deep eutectic solvents as dispersion media, and lignin as fillers and functional additives, and utilizes the hydrogen bonding between the gel and other components to improve the toughness of the gel, so that the flexible sensing device is evenly stressed, the sensing signal is more stable, and the working range of the gel sensor is broadened.
[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0031] (1) The lignin deep eutectic gel provided by the present invention has the advantages of excellent electrical conductivity, low vapor pressure, low cost, easy preparation, and green environmental protection. The deep eutectic solvent has a strong solubility for acrylamide, and the final prepared gel has an electrical conductivity of 0.04S / m, can be stored for a long time in a dry environment at room temperature, and still maintains excellent conductivity, flexibility and adhesion even in a low temperature environment.
[0032] (2) The gel prepared by mixing deep eutectic solvent and lignin in the present invention has extremely strong adhesion properties. The catechol group of lignin can continuously produce sticky substances. The adhesion strength of fresh pig skin simulating human skin is as high as 0.15kPa. At the same time, it can also produce stable adhesion effects with materials such as cotton cloth, glass and plastic. Lignin also enhances the mechanical properties of the gel, broadening the scope of application of gel sensors.
[0033] (3) The conductive gel prepared by the present invention can be used as a biological electrode patch to realize human motion monitoring. At the same time, it can be used as a conductor and assembled into a resistive strain sensor to realize multifunctional sensing. The working range of the strain sensor can reach 400%, and it has good sensing performance in an ultra-wide temperature range of -20-80℃. It has great potential in the fields of human health monitoring, motion monitoring, high and low temperature harsh environment monitoring, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the impedance diagram of the lignin deep eutectic gel prepared by using different ratios of zinc chloride and ethylene glycol in Example 1 of the present invention.
[0035] Figure 2 This is the impedance diagram of the lignin deep eutectic gel prepared by using different contents of sodium lignin sulfonate in Example 2 of the present invention.
[0036] Figure 3 This is the stress-strain diagram of the lignin deep eutectic gel prepared by using different contents of sodium lignin sulfonate in Example 2 of the present invention.
[0037] Figure 4 This is a comparison chart of the shear strength generated by the lignin deep eutectic gel prepared in Example 2 of the present invention and different materials.
[0038] Figure 5 This is a test diagram of the adhesion of the lignin deep eutectic gel prepared in Example 2 of the present invention to a 50mL beaker, a 100mL beaker, an ear bulb, a reagent bottle, and a testing machine fixture (from left to right in sequence).
[0039] Figure 6 This is a graph showing the change in cyclic tensile signal of the lignin deep eutectic gel prepared in Example 2 of the present invention at a strain of 200%.
[0040] Figure 7 This is a room temperature signal change diagram of the lignin deep eutectic gel prepared in Example 2 of the present invention under strains of 100%, 200%, 300%, and 400%.
[0041] Figure 8 This is a low temperature (-20°C) signal change diagram of the lignin deep eutectic gel prepared in Example 2 of the present invention at strains of 100%, 200%, 300%, and 400%.
[0042] Fig. 9 This is a high temperature (80°C) signal change diagram of the lignin deep eutectic gel prepared in Example 2 of the present invention at strains of 100%, 200%, 300%, and 400%. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0044] Unless otherwise defined, all technical terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.
[0045] Example 1
[0046] A lignin deep eutectic gel, the preparation method of which comprises the following steps:
[0047] (1) The hydrogen bond acceptor zinc chloride and the hydrogen bond donor ethylene glycol were mixed in a molar ratio of 1:14, and heated at 60° C. under argon atmosphere for 4 h to obtain a deep eutectic solvent.
[0048] (2) 0.2 g of sodium lignin sulfonate and 4.5 g of acrylamide were placed in 5 mL of the deep eutectic solvent prepared in step (1), and stirred to mix well to obtain solution B.
[0049] (3) Add N,N-methylenebisacrylamide and ammonium persulfate to solution B, stir vigorously for 10 minutes, and after the solid is completely dissolved, put it into a mold, put it into a vacuum drying oven and heat it at 60°C for 4 hours to obtain a product; wherein the amount of N,N-methylenebisacrylamide is 0.4wt% of acrylamide, and the amount of ammonium persulfate is 1wt% of acrylamide.
[0050] Subsequently, under the condition that other process steps and parameters remain unchanged, the molar ratio of zinc chloride to ethylene glycol was adjusted to 0:1, 1:6, 1:10, and 1:18, respectively, to prepare the lignin deep eutectic gel, and the conductivity test was carried out. The specific steps are as follows: the sheet-like lignin deep eutectic gel was cut into 16 mm diameter discs using a 16 mm diameter puncher, and its thickness was measured with a vernier caliper. The cut gel slices were then placed in a battery box with an inner diameter of 16 mm, clamped with an electrode clamp, and then the conductivity and impedance were tested using an electrochemical workstation Electrochemical Instrument (Autolab PGSTAT302N) at a frequency range of 10 -6 -10 -1 Hz, voltage is 100mV. The test results are shown in Table 1 and Figure 1 The results show that the conductivity of the deep eutectic gel is the highest when the molar ratio of hydrogen bond acceptor zinc chloride to hydrogen bond donor ethylene glycol is 1:14.
[0051] Table 1 Effect of different ratios of hydrogen bond acceptors to hydrogen bond donors on conductivity
[0052] Molar ratio of hydrogen bond acceptor to hydrogen bond donor Conductivity (S / m) 1:14 <![CDATA[1.2×10 -2 ]]> 0:1 <![CDATA[1.3×10 -3 ]]> 1:6 <![CDATA[4.4×10 -3 ]]> 1:10 <![CDATA[6.9×10 -3 ]]> 1:18 <![CDATA[2.3×10 -3 ]]>
[0053] Example 2
[0054] A lignin deep eutectic gel, the preparation method of which comprises the following steps:
[0055] (1) The hydrogen bond acceptor zinc chloride and the hydrogen bond donor ethylene glycol were mixed in a molar ratio of 1:14, and heated at 60° C. under argon atmosphere for 4 h to obtain a deep eutectic solvent.
[0056] (2) 0.6 g of sodium lignin sulfonate and 4.5 g of acrylamide were placed in 5 mL of the deep eutectic solvent prepared in step (1), and stirred to mix well to obtain solution B.
[0057] (3) Add N,N-methylenebisacrylamide and ammonium persulfate to solution B, stir vigorously for 10 minutes, and after the solid is completely dissolved, put it into a mold, put it into a vacuum drying oven and heat it at 60°C for 4 hours to obtain a product; wherein the amount of N,N-methylenebisacrylamide is 0.4wt% of acrylamide, and the amount of ammonium persulfate is 1wt% of acrylamide.
[0058] Subsequently, under the condition that other process steps and parameters remain unchanged, the mass volume ratio of sodium lignin sulfonate to deep eutectic solvent is adjusted to 0-0.16 g / mL, lignin deep eutectic gel is prepared, and the conductivity and impedance tests are carried out according to the method in Example 1. The test results are shown in Tables 2 and Figure 2The results show that the conductivity of lignin deep eutectic gel is the highest when the mass volume ratio of sodium lignin sulfonate to deep eutectic solvent is 0.12 g / mL.
[0059] Table 2 Effect of different lignin and deep eutectic solvent ratios on conductivity
[0060] Mass volume ratio of lignin to deep eutectic solvent Conductivity (S / m) 0.12:1 <![CDATA[3.9×10 -2 ]]> 0:1 <![CDATA[2.1×10 -3 ]]> 0.04:1 <![CDATA[1.2×10 -2 ]]> 0.08:1 <![CDATA[2.2×10 -2 ]]> 0.16:1 <![CDATA[9×10 -3 ]]>
[0061] Verification Example 1
[0062] Take the lignin deep eutectic gel prepared in Example 2 and / or the lignin deep eutectic gel prepared based on different lignin and deep eutectic solvent mass volume ratios (0-0.16g / mL) and perform stress-strain test, adhesion test, cyclic tensile test, and wide temperature sensing test. The specific steps of the stress-strain test are as follows: the lignin deep eutectic gel is made into strips with a specification of 50×10×2mm, and then a tensile test is performed at room temperature using a universal testing machine (CMT6203), and the tensile speed is 50mm / min; the specific steps of the adhesion test are as follows: the lignin deep eutectic gel prepared in Example 2 is combined with four representative substrate materials of pig skin, cotton cloth, glass and plastic, and a lap shear test is performed using a universal testing machine (CMT6203), and the tensile speed is 100mm / min; the specific steps of the cyclic tensile test are as follows: the lignin deep eutectic gel sensor prepared in Example 2 is measured using a universal testing machine (CMT6203) and a Keithley 2000MUL The cyclic tensile test was carried out by using a universal testing machine (CMT6203) and a Keithley 2000MUL TIMETER. The universal testing machine was in programming mode, with a tensile speed of 100 mm / min and a strain of 200%. The test was repeated to test the stability of the sensing signal. The specific steps of the wide temperature sensing test were as follows: the lignin deep eutectic gel prepared in Example 2 was subjected to sensing tests at different temperatures (room temperature, -20°C and 80°C) by using a universal testing machine (CMT6203) and a Keithley 2000MUL TIMETER. The universal testing machine was in programming mode, with a tensile speed of 100 mm / min, and the signal changes at strains of 100%, 200%, 300% and 400% were tested.
[0063] The stress-strain test results are shown in Table 3. The results show that the lignin deep eutectic gel with a lignin content of 0.12 g / mL has the best mechanical properties.
[0064] Table 3 Effects of different lignin and deep eutectic solvent ratios on stress and strain
[0065] Mass volume ratio of lignin to deep eutectic solvent Maximum stress (MPa) Maximum strain (%) 0.12:1 0.276 1128 0:1 0.088 329 0.04:1 0.121 542 0.08:1 0.159 772 0.16:1 0.204 906
[0066] The adhesion test results are shown in Table 4 and Figure 4 The lignin deep eutectic gel prepared in Example 2 was subjected to adhesion tests with common items. The results showed that it could adhere to and lift up a 50 mL beaker, a 100 mL beaker, an ear bulb, a reagent bottle, and a test machine fixture, proving that it has excellent adhesion properties (see Figure 2). Figure 5 ).
[0067] Table 4 Lignin deep eutectic solvent adhesion performance test results
[0068] Detection object Adhesion strength (kPa) Pigskin 0.15 cotton 0.22 Glass 0.40 plastic 0.12
[0069] The results of the cyclic tensile test are as follows Figure 6 The results show that the sensing signal of the lignin deep eutectic gel prepared in Example 2 is stable and has good repeatability during the 200% reciprocating stretching process.
[0070] The wide temperature sensing test results are as follows Figure 7-9 The results show that the lignin deep eutectic gel prepared in Example 2 exhibits excellent, stable, and highly sensitive sensing response in the range of 1-400%, whether at room temperature or at harsh ambient temperatures (-20°C and 80°C), and the sensing response increases with the increase in deformation, confirming its application potential in the fields of human health monitoring, sports monitoring, and high and low temperature harsh environment monitoring.
[0071] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a lignin deep eutectic gel, characterized in that: The steps include: (1) mixing a hydrogen bond acceptor and a hydrogen bond donor, and heating the mixture to obtain a solution A; (2) placing lignin and a gel precursor in solution A and stirring and mixing them uniformly to obtain solution B; (3) Add the crosslinking agent and initiator to solution B, stir vigorously to make it uniform, and then heat to polymerize.
2. The preparation method according to claim 1, characterized in that: The hydrogen bond acceptor in step (1) is selected from one or more of lithium chloride, zinc chloride, magnesium chloride, ferric chloride and aluminum chloride.
3. The preparation method according to claim 1, characterized in that: The hydrogen bond donor in step (1) is selected from one or more of ethylene glycol and propylene glycol.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the hydrogen bond acceptor to the hydrogen bond donor in step (1) is 1:3-20.
5. The preparation method according to claim 1, characterized in that: The lignin in step (2) is selected from sodium lignin sulfonate.
6. The preparation method according to claim 1, characterized in that: The gel precursor in step (2) is selected from one or more of acrylamide, acrylic acid, and N-isopropylacrylamide.
7. The preparation method according to claim 1, characterized in that: The initiator in step (3) is selected from ammonium persulfate.
8. The preparation method according to claim 1, characterized in that: In step (3), the amount of the initiator is 0.1-1 wt% of the gel precursor; the amount of the crosslinking agent is 0.01-0.4 wt% of the gel precursor.
9. The lignin deep eutectic gel prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the lignin deep eutectic gel prepared according to the preparation method according to any one of claims 1 to 8 in the preparation of electronic components.
Citation Information
Patent Citations
Polymerizable deep eutectic gel as well as preparation method and application thereof
CN116396448A
Dual-network deep eutectic gel as well as preparation method and application thereof
CN118027452A
Cited By
Lignin-based conductive eutectic gel as well as preparation method and application thereof
CN120441783A